Preparation of shallot capsules with variations in the ratio and type of encapsulating materials [Produksi kapsul bawang merah dengan variasi rasio dan jenis bahan enkapsulan] - Palupi, Niken Widya; Adilah, Hamasah; Giyarto, Giyarto (Jurnal Teknologi & Industri Hasil Pertanian, 2025)
Shallots (Allium ascalonicum) are a perishable spice crop prone to rapid degradation. One method to extend their shelf life is through encapsulation. Shallot capsules possess the potential to mitigate post-harvest losses and improve the utility of shallots. The encapsulating material and its proportion significantly influence the quality of the capsules. This study employed coacervation techniques using alginate combined with oxidized starch as encapsulating materials. The objective of this research was to evaluate the effect of encapsulant-to-shallot ratios and the influence of different combinations of encapsulants on the quality of shallot capsules. The research was conducted using a Completely Randomized Design (CRD) with a factorial arrangement consisting of two factors and carried out in 3 repetitions. The first factor was the ratio of alginate and photo-oxidized starch, and the second factor was the ratio of encapsulating materials to shallot powder. The research involved the preparation of oxidized starch, shallot powder, and shallot capsules, followed by characterization of the capsules. The evaluated parameters included yield, moisture content, total polyphenol content, encapsulation efficiency, loading capacity, SEM analysis, FTIR analysis, solubility, and a triangle test. Data were analyzed using ANOVA at a significance level of ≤ 5% and the triangle test was analyzed using a one-tailed binomial table (p = 0.001). The results showed that the treatments had a significant effect on yield, moisture content, total polyphenol content, encapsulation efficiency, loading capacity, and solubility. Additionally, the triangle test revealed a statistically significant difference between the two treatments at the 0.1% significance level.